(untitled) (Jurnal Bina Praja, 2021)
The government continues to make paradigm changes to make the government system even better. A rigid and centralized government has now turned into a decentralized government and has an entrepreneurial spirit. For this reason, it is necessary to improve service quality on an ongoing basis for the realization of prime public services. Improvement in the quality of public services is carried out comprehensively and integrated, both internally and externally. It is necessary to make improvements and requires proper management to improve service quality. Information services provided by the Public Service Mall by the Palopo City One-Stop Investment Service (DPMPTSP) is a breakthrough that sought to increase public satisfaction in the city of Palopo. This study investigates how public satisfaction with information services was carried out by Public Service Mall (DPMPTSP). This research uses quantitative research methods with a non-random sampling technique by accidental sampling, namely anyone who coincidentally meets the researcher can be used as a sample. The results of this study indicate that the information services provided by the Public Service Mall DPMPTS Palopo City make the public feel satisfied through indicators; (1), Building an information system (2), Establishing a list of information (3), providing facilities and infrastructure (4), Information complaint services. The contribution of this research is expected to be an innovation in realizing a fast, easy, transparent, sure, and affordable government service process as well as bringing closer and providing broader services to the public.